Three-dimensional evaluation of skeletofacial asymmetry in skeletal class ııı patients treated with double-jaw orthognathic surgery - Sarafopoulou, Stavroula (My University, 2018)
ÇİFT ÇENE CERRAHİSİYLE TEDAVİ EDİLMİŞ İSKELETSEL SINIF III HASTALARDAKİ YÜZ ASİMETRİSİNİN 3 BOYUTLU DEĞERLENDİRİLMESİStavroula SARAFOPOULOUYrd. DoçDr. Kadir BEYCANAMAÇ: Bu çalışmanın amaçı ortognatik cerrahi ile tedavi edilmiş iskeletsel sınıf III hastalarda cerrahi öncesi ve sonrasındaki iskeletsel asimetrinin CBCT kullanılarak incelenmesidir.GEREÇ VE YÖNTEM: Bu çalışmada Marmara Üniversitesi Diş Hekimliği Fakültesi Ortodonti anabilim dalında ortodonti ve ortognatik cerrahi ile tedavi edilen 20 adet iskeletsel sınıf III hastanın (5 erkek, 15 kadın, ortalama yaş 22,35±5,16) CBCT kayıtları kullanılmıştır. Tüm hastaların CBCT kayıtları cerrahiden önce ve cerrahiden 4-6 ay sonra alınmış ve Mimics 19.0 yazılımıyla analiz edilmiştir. Asimetriyi değerlendirmek için morfometrik midsagital düzlem rehber alınmıştır. 50 iskeletsel, yumuşak doku ve dişşel landmarkın yeri uzayın 3 yönünde hesaplanarak belirlenmiştir. Ayrıca iskeletsel, dişsel ve yumuşak dokulardaki iskeletofasiyal asimetri; doğrusal ve açısal ölçümlerle değerlendirilmiştir ve yüzde asimetri oluşumuna yardımcı olan olası faktörlerin niceliği belirlenmiştir. Son olarak burun asimetrisi ve cerrahi sonrası burun çevresindeki değişim değerlendirilmiştir.BULGULAR VE SONUÇ: Cerrahi öncesi, Koronoid, Genial Tüberkül, Gonion, yumuşak doku Gonion belirgin asimetri gösterdi. Cerrahi sonrası, Koronoid, Kondil, Gonion, Mandibular korpus uzunluğu ve Gonial bölgedeki yumuşak dokuda rezidüel asimetri bulundu. Kondil ve Koronoid asimetrisi, Gonial bölgedeki asimetri, Ramus uzunluğu, Lateral ramal eğimdeki farklılık; Menton bölgesindeki deviasyonla ilişkilidir. Alar taban, Interalar ve Internostril genişlik ortognatik cerrahi sonrası artma eğilimindedir. Nasiolabial açı; maxillar ilerletme cerrahisi sonucu artma eğilimindeyken, maxiller gömülme cerrahisi sonrası azalma eğilimindedir. Bilgisayar destekli cerrahi simulasyon ile 3 boyutlu teşhiş yapılmıştır ve sınıf III asimetri vakalarında daha iyi ve doğru tahmin edilebilen sonuçlar verdiğinden kişiye özgü burun karakteristiğinin değerlendirmesi yapılmıştır.

THREE-DIMENSIONAL EVALUATION OF SKELETOFACIAL ASYMMETRY IN SKELETAL CLASS III PATIENTS TREATED WITH DOUBLE-JAW ORTHOGNATHIC SURGERYStavroula SARAFOPOULOUAsst. Prof. Dr. Kadir BEYCANAIM: The purpose of this study is to investigate pre- and postsurgically the skeletofacial asymmetry of skeletal Class III, orthognathically treated patients, using Cone-Beam Computed Tomography (CBCT).MATERIALS AND METHODS: The sample of this retrospective study consists of CBCT records of 20 skeletal Class III patients (5 males, 15 females, mean age 22,35±5,16 years), who underwent combined orthodontic and surgical treatment at the Department of Orthodontics, Faculty of Dentistry, Marmara University. The CBCTs of all patients, taken before and after 4-6 months postoperatively, are analyzed by Mimics 19.0 software. In order to assess the asymmetry, a morphometric midsagittal plane is conducted and landmark displacement of 50 skeletal, dental and soft tissue landmarks is calculated in all three planes of space. Moreover, the skeletofacial asymmetry is assessed by linear and angular measurements of the skeletal, dental and soft tissue structures and possible factors contributing to the appearance of facial asymmetry are quantified. Finally, the asymmetry of the nose and the postoperative changes in the nose area are evaluated.RESULTS AND CONCLUSION: Preoperatively, Coronoid, Genial tubercle, Gonion and soft tissue Gonion presented significant asymmetry. Residual asymmetry was found, postsurgically, in Coronoid, Condyle, Gonion, Mandibular body length and soft tissue Gonial area. Condyle and Coronoid asymmetry, asymmetry in Gonial area, Ramus length and Lateral ramal inclination discrepancy were correlated with Menton deviation. Alar base, Interalar and Internostril width tend to increase after the orthognathic surgery. Nasiolabial angle has a tendency to decrease after maxillary impaction, whereas it increases in maxillary advancement. 3d diagnosis achieved with computer-aided surgical simulation and evaluation of individual nasal characteristics are indicated since they deliver better and more predictable outcomes in the treatment of Class III asymmetric cases.
Keywords: Asimetri; Class III; Morfometrik Asymmetry; Morphometrics; Orthodontics; Orthognathic surgery; Ortodonti; Ortognatik Cerahi; Sınıf III